Conséquences physiologiques de l'entraînement en hypoventilation volontaire réalisée à de faibles volumes pulmonaires - Woorons, X. (2007)
We showed that voluntary hypoventilation (VH) at low pulmonary volumes could lead to a drop of arterial oxygen saturation down to 87% during submaximal exercise. We also reported that this severe hypoxemia was accompanied by a significant increase in CO2 pressures, demonstrating that this respiratory technique has both a hypoxic and a hypercapnic effect. After a 4-week training with VH at functional residual capacity, we did not find any change in aerobic metabolism or performance. On the other hand, despite a moderate exercise intensity during training, the maximal blood lactate concentration was maintained after the training period. Furthermore, we found a higher pH and bicarbonates concentration in blood at 90% of maximal heart rate after training. Thus, the main effect of training with VH at low pulmonary volumes would be to delay blood acidosis, possibly thanks to a better buffer capacity. This phenomenon should have a significant positive impact on anaerobic performance.